The Influence of Customer Incivility and Coworker Incivility on Job Satisfaction with The Mediation of Emotional Exhaustion - Desi Rai Sahputri; Ahyakudin Ahyakudin (PT. EQUATOR SINAR AKADEMIA, 2023)
This study aims to determine the influence of customer incivility (X1) and coworker incivility (X2) on job satisfaction (Y) with emotional exhaustion as a mediating variable (Y) among frontline employees at The Royale Krakatau Hotel Cilegon with 50 respondents. This research used a quantitative approach with a census sampling method and analyzed the data using Partial Least Square (PLS) method. The results showed that there was a significant influence of customer incivility on job satisfaction, coworker incivility had a significant relationship with job satisfaction. Moreover, the results also showed that emotional exhaustion had a significant influence on job satisfaction. Additionally, the results indicated that emotional exhaustion significantly mediated the relationship between customer incivility and job satisfaction. Furthermore, the results showed that emotional exhaustion significantly mediated the relationship between coworker incivility and job satisfaction.